Pola Hubungan Antara Jumlah Kelahiran Dengan Jumlah Betina dan Pejantan Produktif Pada Ternak Sapi - Basir Paly (Biogenesis: Jurnal Ilmiah Biologi, 2013)
This research aims to know the pattern of the relationship between the number of births and the number of males and females productive. Implemented in the Gowa in June-October 2014. Using method of survey through observation and interview. The population of the research was a wholegroup of cattle there. As many as 5 group of cattle has been observed and interviewed. Variables are observed and analyzed are: (1) the number of cattle owned by males and females, (2) the number of births, (3) the number of males and females productive, (4) sales, cut withholding, and cases of death,and (5) number of females productive female rescue. Data analysis was carried out in two categories, descriptive and inferensial. Descriptive analysis using a matrix, tabulate and a chart, while inferential analysis using SPSS and Amos 16 software, then validated with data and information from othersources. The results showed that there are four variables that are directly related to the number of births. Namely: (1) the number of female productive, (2) number of females sold, cut withholding, and death, (3) number of productive female rescue, and (4) the number of male productive. To four variables are also interrelated with one another, but not directly related to the number of births. This powerful relationship patterns indicate that the number of births is very closely related to the number of productive female rescue, and the number of males. While the weak relationship patterns indicate that the number of females sold, cut withholding, and the dead, is not related to the number of births.Keywords: birth, females, males, relationships